French Revolution: Looting of the Hotel de Castries in the suburb St Germain in Paris: the November 13, 1790 - Unknown:::Creator::::::::::::
Plate no. 26 from a set of engravings of the French Revolution: Looting of the Hotel de Castries in the suburb St Germain in Paris: the November 13, 1790